Sayid Syekh Al-Hadi: Ahli Kalam Dan Pelopor Harakat Pembaharuan - amir, ahmad nabil (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Singaperbangsa Karawang, 2025)
The paper discusses the work of Sayid Syekh al-Hadi (1867-1934) the leading advocate of Pan Islamic movement and Islamic reform in Malaya that espoused the modern ideal of Sayid Jamal al-din al-Afghani. It looks into his interpretation of religious ideal that underlie his vision of reform and renewal based on his journal articles and novels that response to the traditional practice and customs of the Malays. In this regard, it analyzed aspects of reform that he developed which included the contested ideas of religious orthodoxy, dogma and rituals, modern Islamic consciousness, independent reasoning and ijtihad, current socio-political condition and its underdevelopment and womens’ empowerment and liberation. The study is qualitative in nature based on library and documentary survey. The finding shows that al-Hadi had left behind modern impression of reform that aspired to bring socio-political and cultural progress in contemporary society and raising awareness of the higher value of Islamic spirituality and its liberal, progressive and dynamic implications for society.